Adaptação estratégica no processo de formação do aglomerado de confecções de Colatina - Campana, Juliano Silva (2003)
Colatina now is one of the most important clusters of the branch of makings of Brazil. As all the clusters, its origin doesn't possess a defined cause. However, the growth processes and development happened in a structured way and organized, what facilita